Assessment of Conflicts of Interest in Studies of Breast Implants and Breast Implant Mesh. (25th January 2021) - Tian, Tina; Sekigami, Yurie; Char, Sydney; Bloomenthal, Molly; Aalberg, Jeffrey; Chen, Lilian; Chatterjee, Abhishek
Abstract: Background: With increased collaboration between surgeons and industry, there has been a push towards improving transparency of conflicts of interest (COI). Methods: A literature search identified all articles published between 2016 – 2018 involving breast implants/implantable mesh from three major United States plastic surgery journals. Industry payment data from 8 breast implant/implantable mesh companies was collected using the CMS Open Payments database. COI discrepancies were identified by comparing author declaration statements with payments >$100.00 found for the year of publication and year prior. Risk factors for discrepancy were determined at study and author levels. Results: A total of 162 studies (548 authors) were identified. 126 (78%) studies had at least one author receive undisclosed payments. 295 (54%) authors received undisclosed payments. Comparative studies were significantly more likely to have COI discrepancy than non- comparative studies (83% vs 69%, p < 0.05). Multivariate analysis showed no association between COI discrepancy and final product recommendation. Authors who accurately disclosed payments received higher payments compared to authors who did not accurately disclose payments (median $40, 349 IQR 7278-190, 413 vs median $1300 IQR 429-11, 1544, p <0.001). Conclusions: The majority of breast implant-based studies had undisclosed COIs. Comparative studies were more likely to have COI discrepancy. Authors who accurately disclosed COIs received higher payments than authors with discrepancies. This study highlights the need for increased efforts to improve the transparency of industry sponsorship for breast implant-based studies.